Investment Repercussions: A Comment - Hahn., Dorothy (Quarterly Journal of Economics, 1949)
Investment Repercussions: A Comment Get access Dorothy Hahn Dorothy Hahn University of Birmingham, England Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 63, Issue 3, August 1949, Pages 430–432, https://doi.org/10.2307/1882264 Published: 01 August 1949